Vancomycin-associated Henoch-Schönlein purpura. Issue 3 (March 2017) - Min, Zaw; Garcia, Raquel R.; Murillo, Monika; Uchin, Jeffrey M.; Bhanot, Nitin
Abstract: Intravenous vancomycin is a widely used antibiotics, but it causes different types of cutaneous hypersensitivity reactions, ranging from maculopapular rash, red-man syndrome, drug rash with eosinophilia and systemic symptoms, IgA bullous dermatosis, leukocytoclastic vasculitis, Stevens-Johnsons syndrome, to IgE-mediated anaphylaxis. We report an elderly patient with the end-stage renal disease presented with diffuse palpable purpura while receiving IV vancomycin therapy for methicillin-resistant Staphylococcus aureus septicemia. Histopathology of skin biopsy revealed perivascular infiltrates of leukocytoclastic debris with necrosis of the small-sized blood vessels. Direct immunofluorescence analysis demonstrated vivid IgA plus C3 immune-complex deposits localized to the vessel walls, and no immune complexes were noted on the dermoepidermal junction. There was no IgG or IgM immunoreactivity detected on the tissue specimen. Rheumatologic disease work-ups were negative. A diagnosis of vancomycin-associated Henoch-Schönlein variant of vasculitis was made. Vancomycin was substituted by daptomycin, and the purpuric skin rashes were resolved. Since vancomycin is a commonly used antibacterial agent, clinicians are encouraged to have a heightened awareness of this rare adverse skin reaction. Early recognition and prompt discontinuation of the medication is the key in management. As it is not an Ig-E mediated reaction, desensitization of vancomycin or re-challenge with vancomycin is not recommended as re-exposure to the drug may result in a recurrence of similar manifestations with potential permanent renal failure.